(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the nutritional status of inpatients with chronic obstructive pulmonary disease (COPD) at Thai Nguyen National Hospital in 2025. Subjects and Methods: A cross-sectional descriptive study was conducted on 104 COPD inpatients at Thai Nguyen Central General Hospital. The prevalence of malnutrition was assessed using the Body Mass Index (BMI) and the Subjective Global Assessment (SGA) for malnutrition risk. Anemia status was determined based on patients’ hemoglobin levels. Results: The mean age of participants was 70.56 ± 11.32 years, with the majority aged 60 years or older (87.5%). Male patients accounted for 89.4%. The prevalence of malnutrition based on BMI was 44.2%; only 3.9% were overweight, and no patients were classified as obese. According to SGA, 60.6% were at mild to moderate risk of malnutrition, and 9.6% were at severe risk. The prevalence of anemia among the patients was 32.7%. Conclusion: Malnutrition and anemia are two prominent issues among COPD patients. However, the prevalence of malnutrition varied depending on the assessment method, with SGA detecting a higher proportion of patients at nutritional risk compared to BMI.